Considerations on Teaching How to Say English - M. Subchan Zein (Buletin Al-Turas, 2007)
Teaching pronunciation might be a bewildering task to do for some teachers as they are lack of experienceconsidering the teaching aspects and techniques. However, It will not be such bewildered task if the teachers recognize some principles of teaching this course. In order to make the teaching process effective, a teacher, then, should bear in mind these considerations,which have been suggested by several experts in English language teaching.